Pengembangan Multimedia Teks Wawanrembug Berbasis Blended Learning pada Siswa VIII - Sutriono Hariadi (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2020)
The learning media that will be developed based on technology is the students' base upload skills in the Wawanrembug text. So it is necessary to support learning media to be able to achieve optimal results. This study aims to develop Multimedia Text Wawanrembug Based on Blended Learning and test the effectiveness of the media. This development research method uses the Four-D model namely Define, Design, Develop, Disseminate and the quality of the media is measured through validity, practicality, and effectiveness. The results of the research analysis concluded that multimedia developed in the form of html-based media, android applications, and categorized powerpoint applications is feasible to use. The average for the experimental class is 82.5 and the control class is 77.9. The percentage of feasibility of the developed media is 83%. This multimedia development is very easy to make because it only has Ms. application. Power point. Multimedia developed combined with Blended Learning (using Google Site) can improve student learning outcomes. Thus, the Multimedia Development of Wawanrembug Text Based on Blended Learning in Class VIII Students can be used as a learning medium for students to learn how to upload Wawanrembug Text.